Hepatic abscesses after adhesiolysis. (2015) - Antonsen, J.; Balachandran, R.; Helgstrand, F.
Highlights: Prolonged ileus can cause bacterial translocation. Development of hepatic abscesses after ileus is possible. Prophylactic antibiotics should always be considered. Abstract: Introduction: Hematogenous spread of bacteria from the bowel due to bacterial translocation has been postulated in animal and trauma studies. This case presents a patient with possible hematogenous bacterial spreading after acute laparotomy. Case presentation: A 57-year old woman was admitted with abdominal pain. A computed tomography showed mechanical small bowel obstruction. A laparotomy was performed showing no contamination, and no bowel resection was performed. The patient was not given any antibiotics during this time. The patient was re-admitted 24 h after discharge with fever, elevated white count and abdominal pain. A computed tomography showed newly developed intrahepatic abscesses. These were treated with antibiotics, and the patient was discharged with follow-up ultrasound showing diminished abscesses. Discussion: This case discusses the possible pathophysiology behind the development of intrahepatic abscesses after small bowel obstruction. Conclusion: Febrilia and pain in upper right quadrant of the abdomen days after a simple operation for bowel obstruction could be caused by translocation of intestinal bacteria and subsequent formation of hepatic abscesses.